2023
DOI: 10.1111/jav.03046
|View full text |Cite
|
Sign up to set email alerts
|

Nest orientation and proximity to snow patches are important for nest site selection of a cavity breeder at high elevation

Abstract: Timing and location of reproduction are central to reproductive success across taxa. Among birds, many species have evolved specific strategies to cope with environmental variability including shifts in timing of reproduction to track resource availability or selecting suitable nest location. In mountain ecosystems, complex topography and pronounced seasonality result in particularly high spatiotemporal variability of environmental conditions. Moreover, the risk of climate-induced resource mismatches is partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In particular, the widely-used MODIS snow products have a resolution of approximately 500 m which can fail to capture the spatial heterogeneity of snow cover induced by solar radiation in steep terrain (Bouamri et al, 2021). A high spatial resolution (∼10 m) is also useful for ecologists to characterize habitats of mountain plants and animals (Dedieu et al, 2016;Alba et al, 2023;Niffenegger et al, 2023). Whereas a remotely sensed SWE is the holy grail of snow hydrology, ecologists have shown that the snow cover duration or melt out date are important predictors of alpine plants productivity, distribution and diversity (Galen and Stanton, 1995;Jonas et al, 2008;Carlson et al, 2015;Choler, 2015;Revuelto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the widely-used MODIS snow products have a resolution of approximately 500 m which can fail to capture the spatial heterogeneity of snow cover induced by solar radiation in steep terrain (Bouamri et al, 2021). A high spatial resolution (∼10 m) is also useful for ecologists to characterize habitats of mountain plants and animals (Dedieu et al, 2016;Alba et al, 2023;Niffenegger et al, 2023). Whereas a remotely sensed SWE is the holy grail of snow hydrology, ecologists have shown that the snow cover duration or melt out date are important predictors of alpine plants productivity, distribution and diversity (Galen and Stanton, 1995;Jonas et al, 2008;Carlson et al, 2015;Choler, 2015;Revuelto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%